Ultrasound-Assisted Extraction of Phospholipids from Palm-Pressed Fiber - Chua, Seong Chea (2009)
The extraction of phospholipids (PL) from palm-pressed fiber (PPF) using ultrasound technology was evaluated and quantified using high performance liquid chromatography coupled with an evaporative light scattering detector (HPLC-ELSD). The PL sample was treated with diol solid phase extraction (SPE) to achieve better separation and higher PL recovery by removing neutral lipids. The types of PL that were considered in the recovery study included phosphatidylethanolamine (PE), phosphatidylglycerol (PG), phosphatidylcholine (PC), and lyso-phosphatidylcholine (LPC). A central composite design (CCD) was employed to study the effect of ultrasound-assisted extraction (UAE) conditions, namely amplitude (20%-90%), cycle (0.2-1.0 W/s), and sonication time (5-30 min), on the PL extraction yield from PPF. The optimum parameters for PL extraction using the ultrasound system were 20% amplitude, 0.2 W/s cycle, and a sonication time of 30 min. Under these optimum conditions, the response values obtained for overall extraction efficiency and individual extraction yield of PE and PC were 110 mg/g, 12570, and 5426 mg/kg, respectively. In the purification of PL, it was observed that acetone can remove oil from the extract. Ethanol was used to fractionate PC and PI, as both PC and PI have different solubility in this solvent. In general, PC is more soluble in ethanol than PI. Therefore, the ethanol extract was the PC-enriched fraction and the ethanol precipitate was the PI-enriched fraction. The sample to ethanol ratio significantly (p < 0.05) affected the purity of PC in the PC-enriched fraction. The best ratio of sample/ethanol (g/mL) was 1:20, which resulted in the highest percentage of the PC fraction, with the highest PC level in the PC fraction and the highest PI level in the PI fraction. The PC-enriched fraction contained 45% PC, 2% PE and 5% PI based on the total extract content, whereas the PI-enriched fraction contained 13% PC, 8% PE, and 60% PI.